A System for Trusted Recovery of Data Based on Blockchain and Coding Techniques. (17th January 2022) - Chen, Jinqian; Yan, Yong; Guo, Shaoyong; Ren, Yinlin; Qi, Feng
Abstract : With the continuous development of information technology, the Internet of Things has also been widely used. At the same time, in the power Internet of Things environment, reliable data is essential for data use and accurate analysis. Data security has become a key factor in ensuring the stable operation of the power grid. However, the power Internet of Things devices is extremely vulnerable to network attacks, leading to data tampering and deletion. Resisting tampering, preventing data loss, and reliably restoring data have become difficult to ensure data security. In order to solve this problem, this paper proposes a trusted data recovery system based on blockchain and coding technology. Data nodes of the power Internet of Things encode key data and back them up to the blockchain network through a data processing server located on the edge. The data processing server performs real-time detection of the data integrity of the data nodes. When the data is tampered with or deleted, the data processing server promptly obtains the corresponding data encoding blocks from the blockchain network, decodes them, and sends them to the data node to complete the data recovery task. According to the test result, the data backup speed of this system is increased by 15.3%, and the data recovery speed is increased by 19.8% compared with the traditional scheme. It has good security and real-time performance. Meanwhile, it reduces the network and storage resource overhead in the data backup and recovery process.